Temperature monitoring for femtosecond laser welded interconnection of MWCNT regular structure on PET substrate. (26th July 2020) - Theogene, Barayavuga; Huang, Chenchen; Cheng, Yang; Ren, Xiaoying; Wei, Fengqi; Yin, Hailong
Abstract: In this article, we determine the impact of laser parameters on the development of a flexible conductive transparent film in multi wall carbon nanotubes (MWCNTs) regular structures fabricated on the PET substrate. Both MWCNT and PET are the attractive material for flexible electronics and technological interest in Micro/Nano-manufacturing. Now day, femtosecond laser irradiation nanojoining with selected surface treatments is introduced as an interface enhancer between MWCNT and the PET. We investigated the femtosecond laser of fused PET. After laser irradiation heating, thermal effects modify the structures, and the properties of MWCNTs at the junction point. The network created by Laser irradiation requires extreme parameters: Laser energy irradiation, the effective laser radius, and preheating temperature. Theoretical calculations show us that 90 mW under laser spot radius of 1.5 mm and preheating temperature of 300 K can generate 433.0845 K as surface temperature enough to connect 1 µm in thick of MWCNTs without damage the PET substrate.